Effect of feeding different levels of DL-methionine and L-methionine on heat shock protein 70 expression and blood parameters in broiler chickens under heat stress condition - Nagaraju, Meenambigay (2016)
Methionine (Met) is a sulphur-containing essential amino acid (AA), and is always supplemented in poultry diet to enhance production. A study was conducted to compare the effects of various levels of DL-Methionine (DL-Met) and L-Methionine (L-Met) (feed grade) on physiological reactions to high ambient temperatures in broiler chickens. A total of 660 one-day-old male broiler chicks (Cobb x Cobb) were used in this study. Birds were randomly assigned in a group of five to 132 battery cages. All birds received a standard broiler starter diet from day 1 to 10 and standard grower diet from day 11 to 21. From day 22 to 42, equal number of birds (12 cages / diet) were fed isocaloric and isonitrogenous diets with various levels of DL-Met or L-Met supplementation; (i) 0% DL-Met or L-Met (as a negative control), (ii) 0.136% DL-Met, (iii) 0.136% L-Met. (iv) 0.153% DL-Met, (v) 0.153% L-Met, (vi) 0.170% DL-Met, (vii) 0.170% L-Met, (viii) 0.187% DL-Met, (ix) 0.187% L-Met, (x) 0.204% DL-Met, or (xi) 0.204% L-Met. For each dietary group, equal numbers of birds (6 cages per diet-temperature subgroup) were subjected to unheated (23oC) or heated (32oC for 6 hours/day) condition. On day 42, 2 birds per cage were randomly selected, killed and, blood [to determine serum levels of corticosterone (CORT) and acute phase proteins [ovotransferin (OVT) and α-1-acid glycoprotein (AGP)] and liver [to determine heat shock protein (HSP) 70 density] samples were collected. Irrespective of diet, heat treatment elevated CORT, OVT, and AGP. Diet had no significant effect on all those parameters. There were significant diets x temperature interactions for HSP 70 density. Birds that were not supplemented with either DL-Met or L-Met were not able to express HSP 70 following heat treatment. In conclusion, other than HSP 70, there was little evidence that L-Met is more efficient than DL-Met, and higher level of methionine supplementation did not improve heat tolerance in chickens.